AKTIVITAS INFUSA KULIT DAUN LIDAH BUAYA (ALOE VERA L.) SEBAGAI PENGOBATAN INFEKSI JAMUR - Rafika Sari (Jurnal Analis Farmasi, 2021)
Dermatophytosis is an infection of tissue containing horny substances, such as the stratum corneum in the epidermis, hair, and nails. The infection is caused by the fungus of the genus Trichophyton, one of which is Trichophyton mentagrophytes. Aloe vera leaves contain saponins and flavonoids which are known to have an antimicrobial effect and inhibit fungi. Antifungal products can be processed in various dosage forms, one of which is spray. This study aims to determine the ability of the preparation of aloe vera L. leaf spray in killing T. mentagrophytes. Aloe vera leaves are made using the infusion method with concentrations of 20%, 40%, 60%, 80%, and 100%. Evaluation of preparations made included organoleptic examination and determination of pH values. Testing of antifungal activity was carried out using the diffusion method. The results showed that the spray produced had a liquid texture with sediment, cloudy yellow, menthol odor, pH on days 0, 7, and 14 had a range of values from 4.5 to 4.7. Aloe vera leaf peel spray preparations have antifungal activity against Trichophyton mentagrophytes with a maximum concentration of 100%.